How physics-based techniques are helping to fight SARS-CoV-2 - Gonzalez, J. C. (2021)
The new coronavirus called severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causes an illness named coronavirus disease 2019 (COVID-19). Physicists along with other scientifics are all together in a counterclock race in order to defeat this novel virus. Physics-based techniques and methods are complementing the results coming from other disciplines such as chemistry, medicine, engineering and biotechnology. Let's take a look to know what physics-based techniques and methods can do to help to fight SARS-CoV-2.